Fine-tuned protein-lipid interactions in biological membranes: exploration and implications of the ORMDL-ceramide negative feedback loop in the endoplasmic reticulum - Dingjan, Tamir; Futerman, Anthony H. (Frontiers in Cell and Developmental Biology, 2024)
Biological membranes consist of a lipid bilayer in which integral membrane proteins are embedded. Based on the compositional complexity of the lipid species found in membranes, and on their specific and selective interactions with membrane proteins, we recently suggested that membrane bilayers can be best described as 'finely-tuned molecular machines'. We now discuss one such set of lipid-protein interactions by describing a negative feedback mechanism operating in the de novo sphingolipid biosynthetic pathway, which occurs in the membrane of the endoplasmic reticulum, and describe the atomic interactions between the first enzyme in the pathway, namely serine palmitoyl transferase, and the product of the fourth enzyme in the pathway, ceramide. We explore how hydrogen-bonding and hydrophobic interactions formed between Asn13 and Phe63 in the serine palmitoyl transferase complex and ceramide can influence the ceramide content of the endoplasmic reticulum. This example of finely-tuned biochemical interactions raises intriguing mechanistic questions about how sphingolipids and their biosynthetic enzymes could have evolved, particularly in light of their metabolic co-dependence.